If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 1) = 5x + -6x Reorder the terms: 7(1 + 3x) = 5x + -6x (1 * 7 + 3x * 7) = 5x + -6x (7 + 21x) = 5x + -6x Combine like terms: 5x + -6x = -1x 7 + 21x = -1x Solving 7 + 21x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7 + 21x + x = -1x + x Combine like terms: 21x + x = 22x 7 + 22x = -1x + x Combine like terms: -1x + x = 0 7 + 22x = 0 Add '-7' to each side of the equation. 7 + -7 + 22x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 22x = 0 + -7 22x = 0 + -7 Combine like terms: 0 + -7 = -7 22x = -7 Divide each side by '22'. x = -0.3181818182 Simplifying x = -0.3181818182
| y^2=6+27 | | x+.15x=4623 | | 2s-3s=65 | | 2x+5/3=9 | | 10x+1=491 | | (x^2)-(10x)+(45)=0 | | 18+99+z=180 | | x(.15)=4623 | | 46=-2(m+4)+m | | 61+y=99 | | 1+24=-5(6x-5) | | 10x^2-8=32 | | (x+2)(x-4)=2 | | 99+x=180 | | x-.15=4623 | | 1+24=5(6x-5) | | y=12.00x+50 | | (3x+11)=(4x-21) | | 5x^2+16x+9=0 | | d=-5t^2+60 | | ln(13x+4)=-1.3 | | 15b^2+22b-6=-14 | | 15b^2+22= | | x^2-2x+31=0 | | (3x-43)=80 | | (m+3)(5m+1)=3(m-4)+7 | | x+x+1+x+1=195 | | -2+4(9-9m)= | | -144r^2+1=0 | | 2x+28= | | (5x^2-11x+9)+(7x-13-3x^2)= | | 4(3x+8)=-21+5 |